Modernising the Ukrainian VET System in line with the European Policy of Lifelong Learning : Interview with Prof. Dr. Valentyna Radkevych, Director of the Institute for Vocational Education and Training in Kiev - Radkevych, Valentyna [Interviewter]; Leu, Snishana [Interviewer]; Eberhardt, Christiane [Interviewer] (My University, 2014)
"The Ukrainian system of vocational education and training faces major challenges. As part of an EU twinning project on the modernisation of vocational education legislation and the development of standards, Germany’s Federal Institute of Vocational Education and Training (BIBB) is contributing to a Danish-German consortium to advise and support the Ukrainian Education Ministry on the implementation of imminent reforms. In the interview, Prof. Dr. Valentyna Radkevych refers to key aspects of this reform process and to opportunities that may arise from the international exchange." (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Reform; Ukraine; Internationale Zusammenarbeit